PENGARUH HUMAN CAPITAL TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA) - Yvonne Agustine Sudibyo (Media Riset Akuntansi, Auditing & Informasi, 2011)
The purpose of this research were to analyze individual capability, individualmotivation, leadership factor, organizational climate will influence the publicaccountants’ performances in CPA Firm at DKI Jakarta. Data were collected bydistributing questionnaires to external auditors working at CPA Firm and only127 respondents returned and used in this research. The result of this researchshowed that individual capability, individual motivation and workgroup effectiveness have no influence on auditor performane, but significant influencefrom leadership and organizational climate. Future research should consider theexperience of auditor in demographic respondent and used sample CPA from other big cities.Keywords: Human capital, individual capability, individual motivation, leadership, the organizational climate, workgroup effectiveness, auditors’performances.